Recent advances of functional heterometallic-organic framework (HMOF) materials: Design strategies and applications - Liu, Jiao; Xue, Juanjuan; Yang, Guo-Ping; Dang, Li-Long; Ma, Lu-Fang; Li, Dong-Sheng; Wang, Yao-Yu (Coordination chemistry reviews, 2022)
This review mainly focuses on introducing the different assembled strategies of the heterometallic-organic frameworks (HMOFs), and highlights the influence of the synergistic effect on their enhanced physical and chemical performances. [Display omitted] •The recent advances are carefully introduced for the functional heterometallic-organic frameworks (HMOFs) in detail.•The assembled strategies are presented to isolate the functional HMOFs, such as such as one-pot synthesis, post-synthetic modification, ion exchange strategy, and grinding method, etc.•This work shows the enhanced performances of HMOFs via the synergistic effect for the adsorption, catalysis, magnetism, and fluorescence, etc.•The conclusion and outlook are given for the future development of HMOF materials.•This review will supply some useful guides for the preparation of new HMOF materials for wide applications in the whole energy landscape. Metal-organic frameworks (MOFs) have different structures and various intrinsic properties, such as large specific surface area, flexible and adjustable structural configurations, coordinately-unsaturated metal center, etc., which facilitate the rapid development and wide application of coordination chemistry, over the past decades, including gas adsorption, catalysis, and magnetism. Although the metals in various regions of the periodic table have been explored to build different monometallic MOFs, the researches about functional heterometallic-organic framework (HMOF) materials have not been particularly in-depth. Compared with monometallic MOFs, some special positions are occupied by the heterogeneous metals in one HMOF, which will result in interesting network topologies, and the excellent synergistic effect between the different metal ions will make the physical and chemical properties to be effectively enhanced. This review mainly focuses on introducing the latest progresses of HMOFs, including the various synthesis strategies, applications and outlooks, which may provide some useful guidance for the preparation of novel HMOF materials and make them widely used in the whole energy landscape.